LETHAL CONCENTRATION OF Saussurea costus WITH BRINE SHRIMP LETHALITY TEST METHOD - Dhigna Luthfiyani Citra Pradana; Hany Yusmaini; Erna Harfiani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The safety of using herbal plant extracts is essential for COVID-19 patients who consume herbal plants daily to increase immunity and overcome the symptoms of the disease. One of the herbal plants used by the community in COVID-19 therapy is Qusthul Hindi (Saussurea costus). The public needs to know the safety of these herbal remedies when consuming them. Therefore it is essential to conduct a toxicity test of Hindi Qusthul extract. Secondary metabolite compounds present in plant extracts can be tested for toxicity in vitro using the Brine shrimp lethality test (BSLT) method using Artemia salina Leach larvae to determine LC50 values. The BSLT method is used to determine biological activities in extract plants, such as cytotoxic activity, phototoxic, enzyme inhibition, and ion regulation, using Artemia salina Leach shrimp larvae as bioindicators. The BSLT method is carried out by observing the mortality rate in Artemia salina Leach shrimp larvae which are given extracts from plants and then incubated for 1x24 hours. The results obtained from this study as an LC50 (Lethal concentration) value of 532.78 ppm. LC50 (Lethal Concentration) value of 532.78 ppm indicates that the concentration of the compound can cause death in Artemia salina Leach by as much as 50%.